2017
DOI: 10.1101/233189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasound Produces Extensive Brain Activation via a Cochlear Pathway

Abstract: SummaryUltrasound (US) can noninvasively activate intact brain circuits, making it a promising neuromodulation technique. However, little is known about the underlying mechanism. Here, we apply transcranial US and perform brain mapping studies in guinea pigs using extracellular electrophysiology. We find that US elicits extensive activation across cortical and subcortical brain regions. However, transection of the auditory nerves or removal of cochlear fluids eliminates the US-induced activity, revealing an in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…At no point during any of the experiments conducted here did we find ultrasound to spontaneously elicit EMG activity. It is not currently clear why this is possible in animal models and not here, but may be due to the parameters used, the size of the skull relative to the pressure field and/or perhaps due to other indirect considerations (Guo et al 2017). Specific parameters have been titrated in these small animal preparations that show preference for either excitation or inhibition (H. King et al 2013;Yoo et al 2011).…”
Section: Comparison To Motor Cortex Animal Studiesmentioning
confidence: 94%
“…At no point during any of the experiments conducted here did we find ultrasound to spontaneously elicit EMG activity. It is not currently clear why this is possible in animal models and not here, but may be due to the parameters used, the size of the skull relative to the pressure field and/or perhaps due to other indirect considerations (Guo et al 2017). Specific parameters have been titrated in these small animal preparations that show preference for either excitation or inhibition (H. King et al 2013;Yoo et al 2011).…”
Section: Comparison To Motor Cortex Animal Studiesmentioning
confidence: 94%
“…For example, there is contradictory evidence about whether the motor responses elicited by UNM are the result of direct modulation of the motor cortex or a by-product of sensory activation. Recently, two independent groups have demonstrated that UNM can produce off-target sensory responses in mice (93) and guinea pigs (94) owing to indirect effects on the auditory system. Although the frequencies used in UNM are inaudible, they may produce mechanical vibrations or shear waves in the brain and skull that can be transmitted to the ears.…”
Section: Sonogenetic Actuation Of Cellular Signalingmentioning
confidence: 99%
“…Continued development of instrumentation and technologies for integrating fMRI with Positron Emission Tomography (PET) [108112], Electro-Encephalography (EEG) [113–116], and Transcranial Magnetic Stimulation (TMS) [117,118] has addressed many of the challenges faced when introducing additional equipment into the MRI environment. Recent work combining MRI with ultrasound may pave the way to integration with transcranial Focused Ultrasound (tFUS) [119], and progress using ultrasound to stimulate neuron populations [120,121] may in the future provide key insights into brain function and neurovascular coupling once the mechanisms of neuronal stimulation are better understood [122,123]. These multi-modal approaches can be used to synergistically merge the hemodynamic signals measured in fMRI with complementary metabolic and electrical signals, and image whole-brain responses to targeted neuromodulation, to both enhance neuronal specificity and map large-scale brain circuitry.…”
Section: Specialized and Multi-modal Mri Scanners For Neurosciencementioning
confidence: 99%